Modeling of plasmon resonance in periodic multilayer structures based on chromium with a surface island layer - Koshelev, Ilya R.; Mukhammad , Asiya I.; Gaiduk , Peter I. (Journal of the Belarusian State University. Physics, 2021)
The optical properties of Cr/Si/Cr and Cr/CrSi2 /Cr structures with periodically located chromium islands are modeled using the finite-difference time domain method. These structures are characterized by the phenomenon of plasmon resonance. The dependences of the intensity and position of the plasmon absorption peak on the thickness and radius of the islands are determined. It was observed that when the island thickness increases to 120 nm, the intensity of the absorption peak increases to 69 % for the Cr/Si/Cr structure and to 55 % for the Cr/CrSi2 /Cr structure. It was found that the peak of plasmon absorption in the spectrum of the Cr/Si/Cr structure is at a shorter wavelength (8.4 µm for Cr/Si/Cr, 11.1 µm for Cr/CrSi2/Cr), and also has a higher intensity (the share of absorbed radiation is 14 % higher compared to the peak of plasmon absorption in the spectrum of the Cr/CrSi2 /Cr structure). The obtained dependences indicate that the Cr/Si/Cr and Cr/CrSi2 /Cr structures can be used as IR detectors.
Keywords: plasmon resonance; periodic island structures; optical absorption spectra